A Single, Shared Triploidy in Three Species of Parasitic Nematodes. Issue 1 (1st January 2020) - Schoonmaker, Ashley; Hao, Yue; Bird, David McK; Conant, Gavin C
Abstract: The root-knot nematodes of the genus Meloidogyne are important and damaging parasites capable of infecting most flowering plants. Within this genus, several species of the Meloidogyne incognita group show evidence of paleopolyploidy in their genomes. We used our software tool POInT, the Polyploidy Orthology Inference Tool, to phylogenetically model the gene losses that followed that polyploidy. These models, and simulations based on them, show that three of these species ( M. incognita, M. arenaria and M. javanica ) descend from a single common hybridization event that yielded triplicated genomes with three distinguishable subgenomes. While one of the three subgenomes shows elevated gene loss rates relative to the other two, this subgenome does not show elevated sequence divergence. In all three species, ancestral loci where two of the three gene copies have been lost are less likely to have orthologs in Caenorhabditis elegans that are lethal when knocked down than are ancestral loci with surviving duplicate copies.